Nanocomposite latexes containing layered double hydroxides via RAFT-assisted encapsulating emulsion polymerization. Issue 7 (18th January 2017) - Perreira, Ana Cenacchi; Pearson, Samuel; Kostadinova, Dessislava; Leroux, Fabrice; D'Agosto, Franck; Lansalot, Muriel; Bourgeat-Lami, Elodie; Prévot, Vanessa
Abstract : Successful encapsulation of LDH nanoplatelets into latex particles. Abstract : Nanocomposite latex particles containing layered double hydroxide (LDH) platelets were synthesized using reversible addition–fragmentation chain transfer (RAFT) seeded emulsion polymerization. A random copolymer of acrylic acid (AA) and n -butyl acrylate (BA) was first synthesized by RAFT polymerization, and then electrostatically adsorbed on both nitrate- and carbonate-intercalated Mg2 Al LDH particles to provide both colloidal stability and reactivatable groups from which the subsequent emulsion polymerization could proceed. The nitrate-intercalated LDH showed higher adsorption capacity than its carbonate counterpart because interlayer nitrate ions (in addition to those on the outer surface) were also displaced by the macroRAFT agent. The two macroRAFT agent-modified LDHs were then engaged in the emulsion polymerization of a hydrophobic monomer mixture (methyl acrylate (MA) and BA, 80/20 wt/wt) to form an encapsulating polymer shell. Cryogenic-transmission electron microscopy (cryo-TEM) showed successful encapsulation of the LDH nanoplatelets in the core of the latex particles, with the use of a hydrolytically-stable cationic initiator proving key to achieving high monomer conversions.